2003
DOI: 10.1021/bi034006n
|View full text |Cite
|
Sign up to set email alerts
|

NMR and CD Spectroscopy Show that Imino Acid Restriction of the Unfolded State Leads to Efficient Folding

Abstract: Protein folding is determined by molecular features in the unfolded state, as well as the native folded structure. In the unfolded state, imino acids both restrict conformational space and present cis-trans isomerization barriers to folding. Because of its high proline and hydroxyproline content, the collagen triple-helix offers an opportunity to characterize the impact of imino acids on the unfolded state and folding kinetics. Here, NMR and CD spectroscopy are used to characterize the role of imino acids in a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
17
0

Year Published

2004
2004
2015
2015

Publication Types

Select...
5
2

Relationship

1
6

Authors

Journals

citations
Cited by 24 publications
(18 citation statements)
references
References 37 publications
1
17
0
Order By: Relevance
“…Experiments performed on a set of host-guest peptides with different tripeptide sequences have shown that GPO sequences fold faster than GAO sequences, but both are good nucleation sequences (35). Further studies have shown that nucleation propensity may also be related to the dynamics of the monomer state with a highly constrained monomer state related to the efficiency of folding (36). The CD and NMR results on peptides T1-892 and T1-892(GAO) 3 indicate that imino acid-rich sequences of the form (GPO) 4 or GPO(GAO) 3 can act as nucleation domains when placed at the C-terminal end of the peptide.…”
Section: Discussionmentioning
confidence: 99%
“…Experiments performed on a set of host-guest peptides with different tripeptide sequences have shown that GPO sequences fold faster than GAO sequences, but both are good nucleation sequences (35). Further studies have shown that nucleation propensity may also be related to the dynamics of the monomer state with a highly constrained monomer state related to the efficiency of folding (36). The CD and NMR results on peptides T1-892 and T1-892(GAO) 3 indicate that imino acid-rich sequences of the form (GPO) 4 or GPO(GAO) 3 can act as nucleation domains when placed at the C-terminal end of the peptide.…”
Section: Discussionmentioning
confidence: 99%
“…The importance of the restriction of imino acids in the unfolded state for the efficient folding of the triple helix has recently been described [96].…”
Section: Conformation Of the Randomly Coiled Chainsmentioning
confidence: 99%
“…S7), the chemical shift of O14(Hα) proton, O14(Hβ1), O14(Hβ2) can be identified using the sequential NOE to the labelled G15(NH) in the 1 H, 1 H-NOESY-15 N-HSQC spectrum as well as the intra-residue NOEs and TOCSY cross-peaks arising from the unlabelled hydroxyproline residue, O14(Hβ1)-O14(Hα) and O14(Hβ2)-O14(Hα). The chemical shift of D16(NH) can be identified from the sequential D16(NH)-G15(Hα1) and D16(NH)-G15(Hα2) NOEs in the 1 H, 1 H-NOESY spectrum, these are necessary to differentiate sequences β(O 14 G 15 D 16 ) and γ(O 14 G 15 P 16 ). Finally, in the case of peptide-γ ( Supplementary Fig.…”
Section: Methodsmentioning
confidence: 99%
“…Such peptides, usually referred to as collagen mimetic peptides (CMPs), have been widely used to study the relationship between amino-acid composition and triple helical stability [12][13][14] , folding rate [15][16][17] and super-helical symmetry [18][19][20] , as well as to identify ligand-binding motifs [21][22][23] and provide the structural basis for their recognition [24][25][26] .…”
mentioning
confidence: 99%